Evaluation of Pedestrians Walking Speeds in Baghdad City (Journal of Engineering, 2014)
This research examines the factors which influence pedestrian's walking speed in Baghdad. the variations in walking speed of pedestrians are related to pedestrian characteristics such as gender, age group, and clothing traditions. Using the established methodology, the counts of pedestrians were performed using manual and video counting. The case study was performed in two streets located in a highly crowded commercial zone at the city center of Baghdad: Al-Karada Dakhel and Al- Sina’a Street. Data were subjected to statistical analysis using IBM SPSS Statistics 19 software. It has been found that Iraqi pedestrians walk slower than other pedestrians in the developed countries or in the region with minimum walking speed of 29.85 m/min. Age, gender, and clothing traditions were found to significantly contribute to pedestrian speed. Pedestrians in the age range from 18-50 years old were the fastest group of pedestrians and pedestrians over 50 years old were the slowest. Male pedestrians had significantly faster walking speeds than female pedestrians did. Pedestrians wearing western style were found to be faster than those wearing Arabic style.